2021
DOI: 10.22271/phyto.2021.v10.i2t.14036
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nutrient management and cultivars on quality of sugarcane juice and liquid Jaggery

Abstract: during 2018-19 and 2019. The experiment consisted three main plots (Cultivars) viz., C1-SNK635, C2-Co-86032 and C3 -Konanakatte and five sub plots (Fertilizers levels) F1 : 75 % RDF, F2 : 100 % RDF, F3 :125 % RDF, F4 : 150 % RDF and F5 : control. The experiment was laid out in Strip Block Design with three replication. The results indicated that the cane yield of plant cane was influenced significantly by RDF levels, and cultivars and their interactions. Juice extraction per cent, brix value, pol %, purity %, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
0
0
Order By: Relevance
“…The statistical analysis showed that the vitamin C content of refrigeration and ambient storage temperature-exposed juices decreases significantly (p < 0:05) throughout the storage time (Figure 1). The degradation of vitamin C was also observed by Marc et al [26] and Emelike and Ebere [27] who did on cashew apple juice and also in other fruits juices by other studies [19,28,29]. Moreover, samples with added preservative had a lower decrease compared to the ones without preservative.…”
Section: Sensory Testsupporting
confidence: 70%
“…The statistical analysis showed that the vitamin C content of refrigeration and ambient storage temperature-exposed juices decreases significantly (p < 0:05) throughout the storage time (Figure 1). The degradation of vitamin C was also observed by Marc et al [26] and Emelike and Ebere [27] who did on cashew apple juice and also in other fruits juices by other studies [19,28,29]. Moreover, samples with added preservative had a lower decrease compared to the ones without preservative.…”
Section: Sensory Testsupporting
confidence: 70%
“…~ 426 ~ One area of interest in organic sugarcane cultivation is its effect on cane yield and jaggery quality. Jaggery, a traditional sweetener derived from sugarcane juice, is widely consumed in many parts of the world due to its distinct flavor and perceived health benefits (Shivashenkaramurthy et al, 2021;Guddadamath et al, 2014) [13,5] . Organic cultivation practices have the potential to influence the yield and quality of sugarcane, thereby impacting the characteristics of jaggery produced from organic sugarcane varieties.…”
Section: Introductionmentioning
confidence: 99%